Internet of Things-based Services Implementation and Challenges in Malaysia: An inquiry - Sidek N.; Ali N. (Mattingley Publishing, 2023)
Mechanical engineering; Test facilities; Challenges; Implementation; Internet of thing (IOT); Key trends; Malaysia; Research trends; Technological advances; Internet of things